An alternate approach to identify key service sectors' contributors: Experiences from Malaysian economy - Al-Amin, A.Q.; Islam, M.; Fei, Y.S.; Kari, F. (Academic Journals, 2010)
This study analyzes the direct and indirect rankings and contribution of service sectors in the Malaysian economy from 1987 to 2005. Two different methodologies, that is (1) direct service intensities, and (2) direct plus indirect service intensities have been used to calculate the service intensity of different industries. It is found that the contribution of overall service sectors is mostly positive and steady during the selected time period. However, the empirical findings are quite appealing to identify rankings based on direct and indirect sectoral contributions. The direct sectoral rankings indicate that the contribution of transport and communication is moved from rank 4 to 1; real estate sector moved from rank 15 to 2; and trade moved from rank 2 to 10 from the year 1987 to 2005. However, the direct and indirect intensities and rankings are indicating different directions over the study period. Therefore, the present study aims at studying the evolving nature of service sectors following on the Leontief input-output analysis with means and coefficients of variation. Here, our second method indicates that the manufacturing ranking was 1 in 1987 and also in 2005; the financial related service ranking was 2 in 1987 and 3 in 2005; the trade ranking was 3 in 1987 and 5 in 2005; and the transport and communication ranking was 4 in 1987 and 2 in 2005. We mostly use direct methods to identify key contributors which may direct wrong indications without other supporting justification. This study can be used to identify key contributors especially for policy formulations in Malaysia and elsewhere.